Implementation of Ethnomathematics-Based Learning in Developing the Science and Mathematics Competencies of Muhammadiyah Students - Tri Bangun Utami; Heny Sri Astutik; Alman Alman (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to describe and analyze the implementation of ethnomathematics-based learning in developing students' science and mathematics competencies at Muhammadiyah Malawili Elementary School. The study was motivated by students' low conceptual understanding, which is attributed to instructional practices that remain predominantly abstract and lack contextual relevance. A qualitative approach with a case study design was employed. The research participants consisted of fourth-grade teachers, students from Classes 4A and 4B, and the school principal. Data were collected through semi-structured interviews, participant observation, and document analysis, and were analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The findings indicate that ethnomathematics-based learning effectively contextualizes mathematical and scientific concepts through the integration of local cultural practices, thereby enabling students to develop a more concrete understanding of these concepts. The major findings include: (1) the effective use of cultural artifacts as instructional media; (2) the pivotal role of teachers in mediating the relationship between local culture and scientific concepts; (3) increased student engagement and learning motivation; (4) the integrated development of science and mathematics competencies; and (5) challenges in implementation, particularly regarding teachers' preparedness and the availability of culturally relevant learning resources. This study contributes to strengthening ethnomathematics as a contextual and pedagogically relevant approach to 21st-century education. The implications highlight the need to enhance teachers' professional capacity, develop culture-based instructional materials, and strengthen school policies that support the integration of local culture into classroom learning. Future research is recommended to investigate the implementation of ethnomathematics across broader and more diverse educational contexts.